Studying Humanitarian Disciplines Using Role Games at Higher Educational Establish - Elena Mikhailovna, Chertakova; G. Sobakina, Tatyana; Thanh Nguyen, Phong; Le Hoang Thuy To Nguyen, Quyen; Dang Bich Huynh, Vy (International Journal of Psychosocial Rehabilitation, 2024)
One of the problems faced by a teacher of higher education is the large volume, lack of time for lectures and necessity of studying the content of the material in a shot period. The role-playing improvisation game is in this regard a rational way of covering a significant amount of content in its interconnected unity. At the same time, the game provides a motivational charge for independent expansion of knowledge on the content of the course beyond. In addition, it is a role-playing game that helps bring the content of any of the taught disciplines closer to the specialty received by students. The game encourages the student to reincarnate into another, makes him "rise above himself," because he plays the role, trying on himself an image that is far from his everyday practice. The article discusses the basic methods of teaching the humanities through the use of role-playing games: brainstorming, business games, case studies, group work, etc. The features of the application of these methods and their importance for future specialists are analyzed.